DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY OF COMPANIES THAT HAVE BIOLOGICAL ASSETS IN PLANTATION SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Candra, Revi; Rani, Wahyu Mustika; Amor, Atika; Gampito, Gampito; Elfadhli, Elfadhli (UIN MAHMUD YUNUS BATUSANGKAR, 2025)
The purpose of this discussion is to analyze how the CSR disclosure of companies that have biological assets in plantation sub-sector companies listed on the Indonesia Stock Exchange in 2022 uses Global Reporting Initiative (GRI).The type of research that the authors use is qualitative research. The data collection technique uses a documentation study in the form of an annual report and sustainability reporting plantation sub-sector companies listed on the Indonesia Stock Exchange for the 2022 period. Data processing was carried out descriptively by reducing data, presenting data, and drawing conclusions based on the GRI method to obtain CSR disclosures in the companies studied.The results of the study concluded that of the 21 plantation sub-sector companies listed on the Indonesia Stock Exchange, only 16 companies provide annual reports and sustainability reporting, while the other 5 companies do not yet have reports due to several reasons, namely: they have not been published by the Stock Exchange, they have not been audited and the companies are bankrupt. Of the 16 companies that have annual reports and sustainability reporting only 14 companies have disclosed CSR according to the GRI while the other 2 have CSR but do not meet the GRI criteria.┬áKeywords: Biological Assets, CSR, GRI.